Effect of congenital color vision deficiency on the ability of optometrists to correctly identify lesions in ocular fundus photographs - Richard C. Trevino; Anna A. Tichenor; Susan Kovacich; Hin Cheung (PLoS ONE, 2025)
Purpose To investigate the influence of color vision deficiency (CVD) on the ability of practicing optometrists to correctly identify lesions in digital color fundus photographs with and without the aid of a commercially available color vision remediation device. Methods This study was conducted at the 2024 annual meeting of the American Academy of Optometry in Indianapolis, IN, USA. The color vision of each subject was assessed using the Konan ColorDx CCT-HD®. Individuals with a score <90 for any cone type were classified as having CVD. Each subject then attempted to correctly identify lesions in a series of 12 digital color fundus photographs. Subjects identified as having CVD repeated the photograph task while wearing EnChroma® indoor lenses. The quality of life (QoL) of each subject was evaluated using a modified version of the Color Blindness QoL survey. Results Fifty-five optometrists completed the study. Forty had normal color vision (CVN) and 15 had CVD. Four of 15 (27%) CVD optometrists were previously unaware of their CVD. Both age and CVD influenced the ability of optometrists to correctly identify lesions. Among CVN subjects, younger clinicians (<39 years) outperformed older ones (p = 0.001). However, among subjects with CVD, age did not significantly affect performance (p = 0.84). Compared across CVD status, younger clinicians with CVD performed worse than their normally sighted peers (p = 0.002) while CVD had little effect among older clinicians (p = 0.23). Performance did not improve with use of the EnChroma lenses. Approximately half (47%) of optometrists with CVD reported difficulties in their daily activities attributed to poor color perception. Conclusions CVD and older age decreased the ability of optometrists to correctly identify lesions in fundus photographs. Performance did not improve with use of the EnChroma lenses. Our findings suggest that CVD may pose a disability to eye care providers. We endorse the recommendation that individuals entering medical practice undergo color vision testing and counseling if a deficiency is found.